MODEL-MODEL PEMBIAYAAN PENDIDIKAN (ANALISIS EFEKTIVITAS DAN EFISIENSI DALAM INSTITUSI PENDIDIKAN) - Mesiono Mesiono; Roslaeni Roslaeni (Jurnal Bilqolam Pendidikan Islam, 2021)
This study aims to describe the basic concepts of education financing and education financing models. The research methodology used is the library research method with analytic descriptive data analysis techniques. The results show that an effective and efficient financing model that can be developed is the Power Equalizing model and the Foundation Plan model because the Power Equalizing model is imposed on very rich districts to pay part of the school taxes they collect back into the state's pocket. The factors that influence the financing of school education are influenced by: 1) rising prices; 2) relative changes in teacher salaries (teacher's sallaries); 3) changes in population and an increase in the percentage of children in public schools; 4) increasing educational standards; 5) increasing age of children leaving school; and 6) increasing demands for higher education (higher education).